Leaving The Comfort Zone : The Adventure of a Lifetime - Van Herck, Olivier, ....-; Agasi, Zoë, ....- (Berlin : Gestalten, 2023)
When you are leaving the comfort zone for an outdoor adventure the most incredible things can happen. This book showcases what it's like to experience the full spectrum of life. From encountering different cultures to embracing the freedom of nature, making friendships, and traversing through new landscapes, this adventure ultimately takes you on a journey of self-discovery. Filled with striking imagery and expert advice, this book details a 40,000-kilometer journey spanning four years across several countries and continents using one's own muscle power. Leaving the Comfort Zone provides valuable firsthand accounts and insights to plan your own expedition, from where to stay, what to eat, and who you might expect to encounter along the way. A vivid chronicle of the human spirit, and what happens when you leave your comfort zone in exploration of the unknown.
Keywords: Marketing; Ondernemen; Sociale media